2016
DOI: 10.1097/prs.0000000000002679
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Role of Infection and Biofilms in Wound Healing: Pathophysiology and Treatment

Abstract: Biofilm formation has a substantial role in chronic wounds. Several diagnostic and therapeutic methods against biofilm are currently being developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 86 publications
0
27
0
5
Order By: Relevance
“…Many factors contribute to delayed wound healing, including diabetes mellitus, vascular insufficiency, local pressure, protease deregulation, reduced growth factor activity, inflammation, and concurrent infection . Infections with bacteria have a particularly deleterious effect on wound healing, especially when the wound already exhibits delayed wound healing . The four most common bacteria in wounds are Enterobacteriaceae family members, Enterococcus species, P. aeruginosa , and Staphylococcus species .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors contribute to delayed wound healing, including diabetes mellitus, vascular insufficiency, local pressure, protease deregulation, reduced growth factor activity, inflammation, and concurrent infection . Infections with bacteria have a particularly deleterious effect on wound healing, especially when the wound already exhibits delayed wound healing . The four most common bacteria in wounds are Enterobacteriaceae family members, Enterococcus species, P. aeruginosa , and Staphylococcus species .…”
Section: Discussionmentioning
confidence: 99%
“…44 Infections with bacteria have a particularly deleterious effect on wound healing, especially when the wound already exhibits delayed wound healing. 45 The four most common bacteria in wounds are Enterobacteriaceae family members, Enterococcus species, P. aeruginosa, and Staphylococcus species. 46 Mixed infections with these bacteria are often observed.…”
Section: Discussionmentioning
confidence: 99%
“…2 Several studies, including those from our own laboratories, have indicated that biofilm infections impair wound healing. 2,[6][7][8]10,11,13,14 Therefore, novel strategies of dismantling biofilms are a primary and immediate need in wound care.…”
Section: Discussionmentioning
confidence: 99%
“…2 In addition to impaired cellular wound healing processes, the presence of biofilm infection derails natural wound healing. [3][4][5][6][7][8][9][10][11][12][13][14] Innovative strategies to combat wound biofilm infection, while promoting healing of hardto-heal wounds, are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…All wounds are colonized to a certain degree, and a major role of the inflammatory phase of wound healing is to bring microbes down to steady-state and innocuous levels [11,36] [37]. Biofilm has the capability to seize nutrients in the ECM, such as carbon, nitrogen and phosphate, to supplement their own growth [38]. Once a full-fledged biofilm is formed, a layer of extracellular polymeric substances (EPS) surrounds and protects them against a vast of "predators" such as macrophages, antimicrobial peptides and antibiotics [39].…”
Section: Wound Infections and Healingmentioning
confidence: 99%